Dissolution test optimization for meloxicam in the tablet pharmaceutical form - Érika de Fátima Silva Oliveira; Roberta de Cássia Pimentel Azevedo; Rudy Bonfilio; Diego Borges de Oliveira; Gislaine Pereira Ribeiro; Magali Benjamim de Araújo (Universidade de São Paulo, 2009)
Meloxicam is a broadly used drug in the therapeutics for the osteoarthritis and rheumatoid arthritis treatments in adults, and it is available in the Brazilian market, as tablet and capsule pharmaceutical forms. The present work aimed to establish conditions for accomplishment of the dissolution test of 15 mg meloxicam tablets (A and B test products), compared with the reference product, since there is no monograph about dissolution assays for meloxicam in official summaries. To optimize the conditions several parameters were tested and, according to obtained results, the use of pH 7.5 phosphate buffer (900mL, at 37 ± 0.5ºC) as dissolution medium, paddle method (apparatus 2), stirring speed of the dissolution medium at 100 rpm and collect time of 60 minutes were considered satisfactory. The samples were quantified by UV spectrophotometric method at 362 nm. The products presented kinetics of first-order. Dissolution efficiency values were of 83.25, 83.73 and 88.10% for the A, B and reference products, respectively. Factors f1 and f2 were calculated and similarity of the tested medicines was demonstrated. The dissolution test was validated presenting selectivity, linearity, precision and accuracy within of the acceptance criteria. O meloxicam é fármaco amplamente utilizado na terapêutica para o tratamento de osteoartrite e artrite reumatóide em adultos, e encontra-se disponível no mercado brasileiro, sob as formas farmacêuticas comprimido e cápsula. O presente trabalho objetivou estabelecer condições para realização do teste de dissolução de meloxicam 15 mg na forma farmacêutica comprimido (medicamentos-teste A e B), comparado com o medicamento de referência, visto que não há monografia para o ensaio de dissolução com meloxicam em compêndios oficiais. Para otimização das condições, diversos parâmetros foram testados e de acordo com os resultados obtidos, a utilização de tampão fosfato pH 7,5 (900mL, a 37 ± 0,5 ºC) como meio de dissolução, aparato 2 (pá), velocidade de agitação do meio de dissolução de 100 rpm e tempo de coleta em 60 minutos, foram considerados satisfatórios. As amostras foram quantificadas por espectrofotometria na região do ultravioleta, a 362 nm. Os produtos apresentaram cinética de primeira ordem. Para a eficiência de dissolução encontraram-se valores de 83,25, 83,73 e 88,10% para os medicamentos-teste A e B e referência, respectivamente. Os fatores f1 e f2 foram calculados, demonstrando haver similaridade entre os medicamentos avaliados. O ensaio de dissolução foi validado apresentando seletividade, linearidade, precisão e exatidão dentro dos critérios de aceitação.